(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Accurate assessment of the ACA (Anterior Chamber Angle) is essential for the diagnosis and management of primary angle-closure disease. Gonioscopy remains the gold standard for angle evaluation but is examiner-dependent and invasive. AS-OCT (Anterior Segment Optical Coherence Tomography), using an anterior segment attachment to a conventional posterior segment OCT, offers a non-contact alternative. This study aimed to compare the diagnostic performance of gonioscopy and AS-att-OCT in assessing narrow anterior chamber angles. Methods: A hospital-based cross-sectional study was conducted at a tertiary care teaching hospital between November 2019 and June 2021. A total of 160 patients with narrow angles identified by Van Herrick grade ≤2 was enrolled. All participants underwent detailed ophthalmic examination, including visual acuity assessment, intraocular pressure measurement, Van Herrick grading, gonioscopy using a Goldmann three-mirror gonioscope, and evaluation with an anterior segment attachment OCT (Carl Zeiss Primus 200). Angle status was assessed in all quadrants, and agreement between the methods was analyzed using kappa statistics. Results: The study population ranged from 26 to 66 years with a mean age of 46.2 ± 10.15 years; 55.6% were males. Blurring of vision, eye ache, and redness were common presenting complaints. Elevated intraocular pressure (>21 mmHg) was observed in 9.38% of patients. Hypermetropia was present in 43.1% of subjects and showed the highest prevalence of angle closure. Gonioscopy detected angle closure in 87.5% of eyes with Van Herrick grade 1, while AS-ATT-OCT detected closure in 78.7%. The superior quadrant showed the highest proportion of closed angles (86.25%). Agreement between gonioscopy and AS-ATT-OCT for detecting angle closure was good (κ = 0.68), whereas agreement of either modality with Van Herrick grading was only fair to poor. Conclusion: Anterior segment attachment OCT demonstrated good agreement with gonioscopy in detecting narrow and closed anterior chamber angles. As a rapid, non-contact, and objective technique, AS-ATT-OCT can serve as a valuable adjunct for anterior chamber angle assessment, particularly in settings where gonioscopy expertise is limited.